Identification of a novel mutation in complement receptor 2 in Chinese familial systemic lupus erythematosus - Yuewu Tang; Yi Luo (Archives of Rheumatology, 2022)
Objectives: This study aims to analyze the relationship between complement receptor 2 (CR2) gene mutation and the clinical phenotype in Chinese familial systemic lupus erythematosus (SLE). Patients and methods: A total of one Chinese familial SLE patients (median age: 30.25 years; range, 22 to 49 years) were included between January 2017 and December 2018. The clinical features and diagnoses of familial SLE patients were analyzed using whole-exome sequencing (WES) of genomic deoxyribonucleic acid (DNA) samples. Sanger sequencing was used to verify candidate mutations detected in the examined family. Results: The mother and her three daughters were diagnosed with SLE. The clinical characteristics showed that the patient and her mother were diagnosed with lupus nephritis. The eldest daughter had decreased renal function and lower serum albumin levels. Immunological index analysis showed that all four patients were positive for anti-SSA and antinuclear antibody (ANA), but that only the second daughter was positive for anti-double-stranded DNA (dsDNA). Complement 3 (C3) was significantly decreased in all patients, while evaluation of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) showed that the second and third daughters had mild active SLE. The mother and eldest daughter were treated with prednisolone combined with cyclophosphamide, while the other two daughters were treated with prednisolone alone. The WES and Sanger sequencing analyses revealed an unreported missense T>C mutation c.2804 in the 15th exon of the CR gene in all four patients. Conclusion: We identified a novel c.2804 (exon 15) T>C mutation in the CR gene of Chinese familial SLE. This mutation was previously reported, suggesting that the CR gene c.2804 (exon 15) T>C mutation is the probable cause of SLE in this family.